Otimização de níveis de tensão nas redes de distribuição considerando a alocação de bancos de capacitores e reguladores de tensão. - Madruga, Ederson Pereira (2011)
The reactive power and voltage level control in distribution networks are routine in a power. The customer s voltage levels legislation, allows to the customers with voltage levels out of the limits stipulated by Brazilian Electricity Regulatory Agency receive financial compensation by inadequate service. The coordinated adjust of the equipment, capacitor banks and voltage regulators allocation along the feeders are usual actions to ensure proper voltage levels to the customers. In Brazil, distribution networks are usually large with numerous and long low-voltage circuits. Based on the networks geo-referenced registers, the proposed algorithm uses computational intelligence techniques to optimize voltage levels and reactive power, considering the primary and secondary network distribution. This work provides a tool that will allow the specialist obtain the most cost-effective to simultaneous capacitor banks and voltage regulators allocation, optimizing the primary and secondary voltage levels in distributions networks, minimizing operating costs and losses.